Tourism in East Caribbean Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper studies recent developments in tourism in the East Caribbean countries (ECC) and reviews government policies to support tourism. The paper also presents a model to explain the movements of tourist arrivals to the region during 1970-86. The estimated model is used to project future tourist arrivals in the ECC.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet